Analysis of Outpatient Admission Procedures in Supporting Service Effectiveness at Kudungga Sangatta Hospital - Nur Asiza (Indonesian Journal of Wiyata Health Administration (IJWHA), 2021)
One of the functions of the medical record of the first Kudungga Sangatta Hospital is the admission of patients to outpatient or inpatient care. Admission procedures Outpatient care is essential to the process of health care in hospitals. This research was conducted with the aim of knowing outpatient procedures to support the efficiency of hospital health record services. The method used by the author is a qualitative research method designed. The research used is a case study. In several studies, problems were found: (1) incomplete information from the patient's side or from the patient's/patient's family point of view for the clerk to enter the data in the registration system, (2) the error was the registration system because the internet network connection was not good when the officer entered patient information. Resolving the problem is carried out by the registrar Disseminate the completeness of patient data, such as a KTP or other KTP and the registrar will try to re-enter patient data in a short time Internet connection network has been repaired.